Penyuluhan Hukum: Pencegahan Tindak Pidana Pencurian dan Keamanan Lingkungan di Kelurahan Lalang Medan Sunggal - Lubis, Anggita; Tanauma, Henry Robi; Dermawan, Haris; Lubis, Junaidi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The high number of theft crimes in urban areas such as in Lalang Village, Medan Sunggal, requires increased public legal awareness. This legal counseling activity for law study program students aims to strengthen citizens' understanding of the legal aspects of theft and effective environmental security strategies. The implementation method is carried out through participatory socialization which includes interactive lectures, case discussions, and simulations of environmental security systems (Siskamling). The results of this activity showed a considerable improvement in citizens' understanding of theft and the right to defend themselves (noodweer), from an average initial understanding of 50% to 85% according to the post-test results. In addition, full awareness was formed among residents to reactivate environmental security posts as a preventive measure. In conclusion, this legal counseling succeeded in encouraging the independence of residents in reducing the risk of crime through synergy between understanding regulations and community-based prevention measures in Lalang Medan Sunggal Village.